RESTORE-IMI 1: A Multicenter, Randomized, Double-blind Trial Comparing Efficacy and Safety of Imipenem/Relebactam vs Colistin Plus Imipenem in Patients With Imipenem-nonsusceptible Bacterial Infections - Motsch, J.; de Oliveira, C. M.; Stus, V.; Köksal, I.; Lyulko, O. O.; Boucher, H. W.; Kaye, K. S.; File, T. M.; Brown, M. L.; Khan, I.; Du, J.; Koung Joeng, H.; et al. (My University, 2020)
negative pathogens. We evaluated imipenem/relebactam for treating imipenem-nonsusceptible infections. Methods. Randomized, controlled, double-blind, phase 3 trial. Hospitalized patients with hospital-acquired/ventilatorassociated pneumonia, complicated intraabdominal infection, or complicated urinary tract infection caused by imipenemnonsusceptible (but colistin- and imipenem/relebactam-susceptible) pathogens were randomized 2:1 to 5–21 days imipenem/ relebactam or colistin+imipenem. Primary endpoint: favorable overall response (defined by relevant endpoints for each infection type) in the modified microbiologic intent-to-treat (mMITT) population (qualifying baseline pathogen and ≥1 dose study treatment). Secondary endpoints: clinical response, all-cause mortality, and treatment-emergent nephrotoxicity. Safety analyses included patients with ≥1 dose study treatment. Results. Thirty-one patients received imipenem/relebactam and 16 colistin+imipenem. Among mITT patients (n = 21 imipenem/relebactam, n = 10 colistin+imipenem), 29% had Acute Physiology and Chronic Health Evaluation II scores >15, 23% had creatinine clearance <60 mL/min, and 35% were aged ≥65 years. Qualifying baseline pathogens: Pseudomonas aeruginosa (77%), Klebsiella spp. (16%), other Enterobacteriaceae (6%). Favorable overall response was observed in 71% imipenem/relebactam and 70% colistin+imipenem patients (90% confidence interval [CI] for difference, –27.5, 21.4), day 28 favorable clinical response in 71% and 40% (90% CI, 1.3, 51.5), and 28-day mortality in 10% and 30% (90% CI, –46.4, 6.7), respectively. Serious adverse events (AEs) occurred in 10% of imipenem/relebactam and 31% of colistin+imipenem patients, drug-related AEs in 16% and 31% (no drugrelated deaths), and treatment-emergent nephrotoxicity in 10% and 56% (P = .002), respectively. Conclusions. Imipenem/relebactam is an efficacious and well-tolerated treatment option for carbapenem-nonsusceptible infections.
Keywords: carbapenem resistant; KPC; nosocomial pneumonia; cIAI; cUTI